Gestión municipal y presupuesto por resultados en la Municipalidad Distrital de Punchana 2022 - Maldonado Flores, Lina Layni (2023)
The general objective of the present, Municipal Management and Budget for Results, was to know if the municipal management and the budget are related. The study was of a basic-non-experimental nature and involved a sample of 40 municipal employees. The results show if they are linked, observing a critical value of 0.002 <0.05, which implies that both require reinforcement to have a positive impact on the population.